Critical review of FDM 3D printing of PLA biocomposites filled with biomass resources, characterization, biodegradability, upcycling and opportunities for biorefineries. (September 2021) - Bhagia, Samarthya; Bornani, Kamlesh; Agrawal, Ruchi; Satlewal, Alok; Ďurkovič, Jaroslav; Lagaňa, Rastislav; Bhagia, Meher; Yoo, Chang Geun; Zhao, Xianhui; Kunc, Vlastimil; Pu, Yunqiao; Ozcan, Soydan; et al.
Highlights: Polylactic acid filled with bioresources can be printed by Fused Deposition Modeling. Recent advancements on printing conditions and mechanical strength are discussed. Characteristics of the biocomposites have been described. Improvements for additive manufacturing of these PLA biocomposites have been proposed. Abstract: 3D printing by fused deposition modeling (FDM) is an advanced additive manufacturing technology for making thermoplastic-based structures. Several studies have recently investigated 3D printing of polylactic acid (PLA) with biomass resources like cellulose, hemicellulose, lignin and whole biomass. Such biodegradable composites are better for the environment and can be used to replace non-biodegradable composites in a variety of applications. Therefore, a deep understanding of printing such biocomposites is needed for supporting such manufacturing. Recent developments focused on FDM printing of PLA filled with biomass resources have been critically reviewed to reveal the intricate aspects of manufacturing of such materials and characterization of the changes caused by biomass-based fillers. Properties of high molecular weight PLA, essentials of printing with PLA and conditions for filament extrusion and printing of biocomposites are discussed. Characterization results from mechanical testing, thermal analysis, viscoelastic properties, imaging and spectroscopy are reviewed for understanding the impact of filling biomass resources in PLA by printing. The latter sections discuss applications, upcycling & recycling and future opportunities for biorefineries. Graphical abstract: Image, graphical abstract